Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian Laptop Asus - Ilham Sembiring; Safaruddin Safaruddin; Desri Wiana; Harris Pinagaran Nst; Anggiat Parlindungan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Nowadays, technological advances are growing rapidly, where every company is competing to create new products and follow the trends of what customers want. This is very influential in facilitating activities carried out by consumers. Laptops are now really needed by students to support their mobility in carrying out assignments and reports that must be done and submitted to their lecturers, especially for final year students to write their theses as graduation requirements. This research aims to examine the influence of product quality and price on the decision to purchase Asus laptops among Medan city students. This researcher needs to know which variable dominates. The type of research used is correlational research. This research is quantitative. The population and sample in this study were 100 students in the city of Medan, data was taken through a questionnaire distributed online to respondents. The independent variables in this research are product quality (X1) and price (X2), while the dependent variable is purchasing decision (Y). Data were analyzed using Instrument Tests, Classical Assumption Tests, and Multiple Linear Regression. The results of this research show that product quality partially has a positive and significant effect on the decision to purchase Asus laptops among students in the city of Medan, while the price variable has no effect on the decision to purchase Asus laptops and simultaneously has a positive and significant effect on the decision to purchase Asus laptops among students in the city of Medan and The more dominant variable in this research is the product quality variable.